Pengaruh Financial Distress terhadap Earning Manajemen di Mediasi oleh Pengaruh Profitabilitas dan Laverange: Studi Perusahaan Manufaktur di BEI Periode 2021-2023 - Setiyo Hadi Santoso; Robiatul Adawiyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study Analyzes The Factors Influencing Earnings Management Mediated by Financial Distress in Consumer Products Manufacturing Companies Listed on The Bursa Efek Indonesia (BEI) During The Period 2021-2023. The objective of this research is to identify the determinants of earnings management and examine the mediating role of financial distress. The research data were obtained from the Bursa Efek Indonesia (BEI) in the form of annual financial statements of consumer product manufacturing firms. A purposive sampling technique was employed, resulting in 13 sample companies out of a total population of 59 firms. Path analysis was used as the analytical method, with SPSS version 22 serving as the data processing tool. Secondary data were collected through documentation by accessing financial reports from the official IDX website (idx.co.id). The findings of this study are expected to demonstrate that financial distress significantly influences earnings management; profitability affects financial distress; and financial distress mediates the relationship between leverage and profitability on earnings management. In addition, leverage is found to influence financial distress but does not have a direct effect on earnings management.